APPLYING EMISSION CONTROL AREAS (ECA) IN MARITIME ZONES: ADOPTION AND COMPLIANCE - Sylvia, Kellyn; Indriyani, Rachma; Muslimah, Siti; Luz, Gustavo Leite Neves da (Tirtayasa Journal of International Law, 2025)
The establishment of Emission Control Area (ECA) constitutes a significant regulatory measure within the international maritime legal framework aimed at mitigating air pollution generated by shipping activities. Pursuant to MARPOL Annex VI, the designation of an ECA requires a comprehensive, evidence-based proposal evaluated by the International Maritime Organization (IMO). Within these designated zones, ships are obligated to utilize low-sulfur fuel or adopt emission reduction technologies to comply with stringent emission standards. The implementation of ECAs has demonstrably contributed to improved air quality in port cities and coastal regions. Compliance is ensured through a multi-level enforcement mechanism involving flag States, port States, and coastal States, supplemented by technological monitoring and regulatory infrastructure. This study adopts a normative legal methodology combined with a descriptive-analytical approach to examine the legal provisions, enforcement mechanisms, and practical implications of ECA implementation in achieving sustainable environmental protection in the maritime sector.